Factors associated to depression and anxiety in medical students: a multicenter study. Issue 1 (December 2016) - Brenneisen Mayer, Fernanda; Souza Santos, Itamar; Silveira, Paulo; Itaqui Lopes, Maria; de Souza, Alicia; Campos, Eugenio; de Abreu, Benedita; Hoffman II, Itágores; Magalhães, Cleidilene; Lima, Maria; Almeida, Raitany; Spinardi, Mateus; et al.
Abstract Background To evaluate personal and institutional factors related to depression and anxiety prevalence of students from 22 Brazilian medical schools. Methods The authors performed a multicenter study (August 2011 to August 2012), examining personal factors (age, sex, housing, tuition scholarship) and institutional factors (year of the medical training, school legal status, location and support service) in association with scores of Beck Depression Inventory (BDI) and State Trait Anxiety Inventory (STAI). Results Of 1, 650 randomly selected students, 1, 350 (81.8 %) completed the study. The depressive symptoms prevalence was 41 % (BDI > 9), state-anxiety 81.7 % and trait-anxiety in 85.6 % (STAI > 33). There was a positive relationship between levels of state (r = 0, 591, p < 0.001) and trait (r = 0, 718, p < 0.001) anxiety and depression scores. All three symptoms were positively associated with female sex and students from medical schools located in capital cities of both sexes. Tuition scholarship students had higher state-anxiety but not trait-anxiety or depression scores. Medical students with higher levels of depression and anxiety symptoms disagree more than their peers with the statements "I have adequate access to psychological support" and "There is a good support system for students who get stressed". Conclusions The factors associated with the increase of medical students' depression and anxiety symptoms were female sex, school location and tuition scholarship. It is interesting that tuition scholarship students showed state-anxiety, but not depression and trait-anxiety symptoms.